Association of circulating vitamin D with colorectal cancer depends on vitamin D-binding protein isoforms: A pooled nested case-control study - Gibbs, D; Song, M; McCullough, M; Perez-Cornago, A; Et al. (Oxford University Press, 2019)
Background: Higher circulating 25-hydroxyvitamin-D [25(OH)D] concentrations are consistently inversely associated with colorectal cancer (CRC) risk in observational studies. However, it is unknown whether this association depends on the functional GC-rs4588*A (Thr436Lys) variant encoding the vitamin D-binding protein-2 (DBP2) isoform, which may affect vitamin D status and bioavailability. Methods: We analyzed data from 1,710 incident CRC cases and 1,649 incidence-density matched controls nested within three prospective cohorts of mostly Caucasians. Study-specific incidence rate ratios (RRs) for associations of pre-diagnostic, season-standardized 25(OH)D concentrations according to DBP2 isoform with CRC were estimated using multivariable unconditional logistic regression and pooled using fixed effects models. All statistical significance tests were two-sided. Results: The odds of having 25(OH)D concentrations below 50 nmol/L (considered insufficient by the Institute of Medicine) were 43% higher for each DBP2-encoding variant (rs4588*A) inherited (per DBP2 OR = 1.43, 95% CI: 1.27 to 1.62, Ptrend = 1.2 x10-8). The association of 25(OH)D concentrations with CRC risk differed by DBP2: 25(OH)D concentrations considered sufficient (≥50 nmol/L), relative to deficient (<30 nmol/L), were associated with a 53% lower CRC risk among individuals with the DBP2 isoform (RR = 0.47, 95% CI: 0.33 to 0.67), but a non-statistically significant 12% lower risk among individuals without it (RR = 0.88, 95% CI: 0.61 to 1.27) (Pheterogeneity = 0.01). Conclusions: Our results suggest that the 25(OH)D-CRC association may differ by DBP isoform, and those with a DBP2-encoding genotype—linked to vitamin D insufficiency—may particularly benefit from adequate 25(OH)D for CRC prevention.